Effects of corn steep liquor supplementation on performance and herbivory patterns of beef Cows Grazing Native Range Infested with Sericea Lespedeza (Lespedeza cuneata) - Garrett W. Preedy; K. C. Olson; Walter H. Fick; Leigh W. Murray (Kansas Agricultural Experiment Station Research Reports, 2014)
Increased grazing pressure on sericea lespedeza by beef cattle, the most economically relevant herbivore in the region, may slow its spread and facilitate some measure of biological control. Unfortunately, mature plants contain high levels of condensed tannins that decrease protein digestion by beef cattle, and these compounds are potent deterrents to grazing. Supplementing corn steep liquor has been shown to alleviate the negative effects associated with ingestion of condensed tannins when beef cattle are fed prairie hay contaminated with sericea lespedeza. In addition, beef cows supplemented with corn steep liquor did not discriminate between sericea lespedeza-contaminated and sericea lespedeza-free prairie hay in a preference trial. Therefore, the objective of our study was to evaluate the effects of supplemental corn steep liquor on herbivory patterns and performance of beef cows grazing native tallgrass rangeland infested with sericea lespedeza.
Keywords: Cattlemen& #x27; s Day; 2014; Kansas Agricultural Experiment Station contribution; no. 14-262-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1101; Beef Cattle Research; 2014 is known as Cattlemen& #x27; s Day; Beef; Lespedeza cuneata; Corn steep liquor; Grazing